IMPACT OF AGRICULTURE PRODUCTIVITY ON ECONOMICS GROWTH: A CASE STUDY OF ASEAN-3 - Pannawadee Radinghin; Shania Temeña; Badara Shofi Dana (UPT Penerbitan Universitas Jember)
The agricultural sector still has a large contribution to economic growth in developing countries such as ASEAN. Because the agricultural sector absorbs high labor and has a large output as a source of economic growth in developing countries. Based on the level of productivity of agriculture sector in ASEAN-3 (Indonesia, Thailand, and the Philippines), this study aims to see the contribution of agricultural sector productivity to economic growth. Variables used as a proxy for agricultural productivity are gross capital formation, agriculture value-add, employment in agriculture sector, inflation and trade openness with economic growth through real gross domestic product per capita. The use of Vector Autoregression (VAR) in this study aims to see the relationship between the agricultural sector with economic growth and the amount of agricultural productivity contribution to economic growth through impulse response function and variance decomposition. The results obtained in this study are the productivity of the agricultural sector has contributed to economic growth in ASEAN-3, where inflation and gross capital formation has the largest contribution in economic growth in Indonesia, the Philippines, and Thailand. The government policy that needs to be paid attention is about the level of price and assistance in the capital of business in the agricultural sector.